Cidade dos Pescadores: etnografia dos pescadores do Mucuripe - Lima, Maria Simone de Oliveira (2018)
Cidade dos Pescadores is an ethnography of the sociocultural relations of the artisanal fishermen of Mucuripe, east coast of the city of Fortaleza. It describes the relationships that are established in daily life, in the forms of community and family coexistence, in their work, leisure and housing spaces. The sociological discussion on living conditions in degraded areas in urban space is part of this work, and for this I turn to thinkers and sociologists to reflect concepts pertinent to urban sociology, in understanding the connections between city and market, city and context of disputes over urban space, the experience of living in the city, even in situations of vulnerability and poverty. Audiovisual record, direct interview and participant observation are articulated as a methodological research strategy. To talk about the Mucuripe is to think about its historical and socio-cultural limits. Historically, artisanal fishermen constitute their first inhabitants. Today, the legacy left by generations of predecessors and the experiences of the present in the activity of artisanal fishing transform these subjects into protagonists of their own history, whether in the occupation of physical spaces for work and housing, or in dealing with the sea in a way sustainable and unbreakable forms of religious devotion. The narratives of this work are fruits of the daily coexistence with fishermen, in the spaces of work, leisure and dwelling, namely in the Barracão, in the Alley of the Carás and in the Hill of Santa Terezinha; the research brings, finally, reflections on the current permanence of these workers in a noble area of the city, where they are daily pushed with their families to peripheral areas, places where they experience inhuman aspects of the disorder of the space and the urban degradation of the city.